Advanced sarcoidosis. Issue 5 (September 2019) - Baughman, Robert P.; Wells, Athol
Abstract : Purpose of review: Advanced sarcoidosis is an important cause of morbidity and mortality in sarcoidosis. Over the past few years, several studies have been published clarifying the prevalence and severity of this condition. Recent findings: Pulmonary involvement is the most common form of sarcoidosis. Increased morbidity and significant mortality is encountered in advanced lung disease. Although many sarcoidosis patients with pulmonary fibrosis have a normal life expectancy, at least 20% develop progression and may die from this complication. Sarcoidosis-associated pulmonary hypertension (SAPH) is an independent cause of death in advanced pulmonary sarcoidosis. Two large multicenter registries and a large single-center report provide more details regarding presentation and outcome of SAPH. Advanced neurologic disease is associated with significant morbidity, but not much mortality. Two large retrospective reviews demonstrated the effectiveness of infliximab in treating advanced neurosarcoidosis. Advanced cardiac sarcoidosis can lead to mortality. Summary: Advanced sarcoidosis is associated with significant morbidity and some mortality. Up to a quarter of all sarcoidosis patients have one or more forms of advanced disease. These patients require closer monitoring and often multiples treatments.